Patient and provider‐level barriers to hepatitis C screening and linkage to care: A mixed‐methods evaluation. Issue 7 (2nd March 2020) - Higashi, Robin T.; Jain, Mamta K.; Quirk, Lisa; Rich, Nicole E.; Waljee, Akbar K.; Turner, Barbara J.; Lee, Simon Craddock; Singal, Amit G.
Abstract: Achieving practice change can be challenging when guidelines shift from a selective risk‐based strategy to a broader population health strategy, as occurred for hepatitis C (HCV) screening (2012‐2013). We aimed to evaluate patient and provider barriers that contributed to suboptimal HCV screening and linkage‐to‐care rates after implementation of an intervention to improve HCV screening and linkage‐to‐care processes in a large, public integrated healthcare system following the guidelines change. As part of a mixed‐methods study, we collected data through patient surveys (n = 159), focus groups (n = 9) and structured observation of providers and staff (n = 9). We used these findings to then inform domains for the second phase, which consisted of semi‐structured interviews with patients across the screening‐treatment continuum (n = 24) and providers and staff at primary care and hepatology clinics (n = 21). We transcribed and thematically analysed interviews using an integrated inductive and deductive framework. We identified lack of clarity about treatment cost, treatment complications and likelihood of cure as ongoing patient‐level barriers to screening and linkage to care. Provider‐level barriers included scepticism about establishing HCV screening as a quality metric given competing clinical priorities, particularly for patients with multiple comorbidities. However, most felt positively about adding HCV as a quality metric to enhance HCV screening and linkage to care. Provider engagement yielded suggestions for process improvements that resulted in increased stakeholder buy‐in and real‐time enhancements to the HCV screening process intervention. Systematic data collection at baseline and during practice change implementation may facilitate adoption and adaptation to improve HCV screening guideline implementation. Findings identified several key opportunities and lessons to enhance the impact of practice change interventions to improve HCV screening and treatment delivery.